Satirical Meanings In The Song â€œThe Israel Dreamâ€ Schleiermacher's Hermeneutic Interpretation Of Israel's Dark Face As The Nemesis Of The Islamic World - Muhammad Robbani Akbar; Abdul Rohman (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2025)
This article analyzes the satirical meaning in The Israel Dream, a song by Mushtofa Al-Mumri, using Schleiermacherâ€™s hermeneutic approach. Although the song appears to support Zionist narratives, it actually delivers sharp criticism against an oppressive ideology that positions the Islamic world as the primary nemesis of the Greater Israel project. The study aims to uncover how linguistic structures and symbolism in the lyrics convey hidden messages filled with socio-political critique. A qualitative descriptive method is used, applying both grammatical and psychological interpretation to examine the text and the composerâ€™s intent. The findings reveal that the lyrics employ irony, metaphor, and narrative impersonation to deconstruct Zionist propaganda from a fabricated internal voice, awakening listeners to its underlying dangers. The song is not merely an artistic expression, but also serves as a form of cultural resistance and spiritual consciousness. This study affirms that music can be a powerful reflective medium in opposing hegemony especially when that hegemony frames Islam as its ideological nemesis.